Algorithm implementation for CNV discovery using Affymetrix and Illumina SNP array data. - Winchester, L; Ragoussis, J (2012)
SNP array data can be analysed for the purpose of calling SNP alleles but also for determining the absolute copy number of a certain genomic segment. Here, the method for detecting copy number (CN) change using intensity data from SNP arrays is focused on. Methods incorporating data from the two main genotyping platforms, Affymetrix and Illumina, are described and possible options and problems that may be faced are examined. We discuss the importance of the quality control when using this analysis method and present some guidelines for implementation, both prior and post to algorithm use. A discussion of algorithms available for CN detection is included as well as ideas for further analysis protocols.